Towards a new model for green consumer behaviour: A self‐determination theory perspective - Gilal, Faheem Gul; Chandani, Kanwal; Gilal, Rukhsana Gul; Gilal, Naeem Gul; Gilal, Waseem Gul; Channa, Nisar Ahmed (Sustainable development (Bradford, West Yorkshire, England), 2020)
Prior research has broadly captured consumers' green behaviour by linking it to either intrinsic or extrinsic motives. Nonetheless, the detailed effects of middle‐ground motives (i.e., external, introjected, and identified) on the formation of green consumer behaviour remain largely untapped in marketing literature. Using two theoretical lenses—organismic integration theory of self‐determination theory and gender schema theory—this study investigates the effects of motivational regulations on consumers' green behaviour using data from Pakistani millennial consumers. To this end, two separate but related studies were conducted. Study 1 involved participants (n = 208) from Sindh province, whereas Study 2 recruited subjects from three other provinces of Pakistan: Punjab, Khyber Pakhtunkhwa, and Balochistan (n = 312). Exploratory factor analysis, confirmatory factor analysis, structural equation modelling, and multigroup modelling techniques were used as methods. Study 1 shows that when intrinsic motivation and three types of extrinsic motivations (i.e., external, introjected, and identified) were examined, identified motivation had the strongest effect on green consumer behaviour. The findings of Study 2 indicated that, compared with males, females responded much more strongly to motivation associated with intrinsic regulation. Likewise, male consumers tended to respond much more strongly to identified and external motivations with regard to their green behaviour. To conclude this study, the implications of these findings are discussed in great detail.